1999
DOI: 10.1002/(sici)1521-3773(19991018)38:20<3043::aid-anie3043>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Promoted Linear Tetramerization and Cyclization of 3,3-Dimethylbut-l-yne

Abstract: With tetrahydrofuran as the solvent [Rh(thf)(2)(cod)](+) promotes the selective coupling of tBuC(2)H to form triene-yne 1; at high alkyne concentrations, however, an unusual C-H activation process intervenes, leading to the formation of complex 2, which contains two linked five-membered rings. cod=1,5-cyclooctadiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 9 publications
1
28
0
Order By: Relevance
“…This reaction has been briefly reported almost 35 years ago, but the synthetic procedure has not been given . We found that the best yield of the fulvene complex 6 (64 %) is achieved after 1 h reaction at 0 °C, while longer reaction times diminish the yield of 6 (38 % for 2 h reaction), presumably, because of the further oligomerization of tert ‐butylacetylene . Reaction of the cationic fulvene complex 6 with the excess of NaBH 3 CN gives the neutral cyclopentadienyl complex 7 .…”
Section: Resultsmentioning
confidence: 90%
“…This reaction has been briefly reported almost 35 years ago, but the synthetic procedure has not been given . We found that the best yield of the fulvene complex 6 (64 %) is achieved after 1 h reaction at 0 °C, while longer reaction times diminish the yield of 6 (38 % for 2 h reaction), presumably, because of the further oligomerization of tert ‐butylacetylene . Reaction of the cationic fulvene complex 6 with the excess of NaBH 3 CN gives the neutral cyclopentadienyl complex 7 .…”
Section: Resultsmentioning
confidence: 90%
“…Two aryl alkynes then sequentially insert to give the metallacyclohexadiene intermediate B, which undergoes reductive elimination to give the fulvene-type species C. Finally, the coordinated ethoxide attacks the exocyclic carbon of the intermediate C to give the ultimate product. On the [2 + 2 + 1] cyclotrimerization of alkynes, two mechanisms have been proposed so far: a metallacyclopentadiene route and a metallacyclohexadiene route [13][14][15][16][17][18][19][20][21][22]. The mechanism involving the metallacyclohexadiene intermediate seems to be appropriate to our case.…”
Section: Reactivity Of 1 With Alkynesmentioning
confidence: 99%
“…By contrast, there have been only a limited number of reports on the formal [2 + 2 + 1] cyclotrimerization of alkynes to give five-membered rings [11][12][13][14][15][16][17][18][19][20][21][22]. Very recently, we reported the reactivity of [Cp * Rh(g 2 -NO 3 )(OTf)] toward terminal aryl alkynes (HAC"CAPh and HAC" CAC 6 H 4 CH 3 ) in alcohol (EtOH and n-BuOH) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since subsequent transformations such as alkenyl-vinylidene isomerization [4] or carbon-carbon couplings via multi-insertion [5] are often encountered, the insertion process receives still considerable attention. Recent investigations on the insertion into the Ir-H bond of trans-[IrH(PPh 3 ) 2 {C(Ph)= CHC(O)Me}(acetone)] + have demonstrated that the outcome depends in a sensible manner on the steric and electronic propensities of the alkyne [6].…”
mentioning
confidence: 99%